SÍNTESE E CARACTERIZAÇÃO DE EMULSÃO POLIÉSTER PROVENIENTE DE RESINA DE PINUS - Correa, Jamille de Souza (2018)
In this study, the purification of colophony was carried out to prepare a polyester emulsion. First, the Pinus resin was purified by washing with distilled water, to remove residual acids from the resin process, and solubilized in ethanol fuel (97%), to filter the resin and remove solid particles (branches, insects and other debris of the forest). Thereafter, the solvent was recovered using a rotary evaporation system. The purification and obtaining of the colophony present in the Pinus resin was carried out by steam drag, and the turpentine (volatile fraction of the Pinus resin) was separated from the colophony (solid fraction). Synthesis of the polyesters was carried out by the esterification reaction between purified rosin, glycerol and maleic and phthalic anhydrides. To compare the influence of colophony on the polyester, another polymer was synthesized, however, without addition of colophony. In order to avoid the use of volatile organic compounds in the final paint product, emulsions were prepared by the catastrophic phase inversion process, where different emulsifier contents, 7% and 10% (m / m) were tested. Infrared and Raman spectra showed the formation of the α, β unsaturated ester group following the syntheses. From the thermograms it was possible to observe that the addition of the colophony contributed to improve the stability of the polymer to the temperature of 380 ° C. Above this temperature, the polyester without colophony showed better stability, decomposing completely at 700 ° C. The polyester with colophony decomposed at 450 ° C. To evaluate the ability to agglomerate pigment particles and the possibility of application as paint, a green pigment of zinc oxide was dispersed in the emulsions. The emulsion with the best performance in the stability tests was the one with emulsifier content of 10%. The pigmented emulsions, when applied on the gypsum test specimens, showed fast drying along with a good surface coating and good pigment dispersion, presenting characteristics suitable for application as coatings of the paint industry.